O SUS que se vê: a atenção básica à saúde nas notícias do telejornalismo de Pernambuco - Silva, Jorge Luiz (2023)
The present research, as a consequence, has the general objective of analyzing the representation of public health, more specifically, of Basic Health Care, in the news published on the ABTV news programs 1st and 2nd Edition of TV Asa Branca, an affiliate of Rede Globo, located in the municipality of Caruaru – Pernambuco, between 2014 and 2016. The specific objectives are to analyze the content of the news about Basic Care in Caruaru in order to verify the representation constructed by the broadcaster regarding basic Health Care at the municipal level; 2) identify the newsvalues adopted by the broadcaster on the public health issue aiming to understand why the news about SUS is the way they are; and finally, 3) comparing the representations built on public health by TV Asa Branca and official documents witch show the public investments that took place in the city of Caruaru in the years 2014, 2015 and 2016 with the purpose of visualizing whether or not there was a mismatch between what was publicized and what happened with regard to social advances in the field of public health in the city, more specifically, Primary Care. Our methodology is based on Content Analysis (Bardin, 2011). The work was divided into two axes of analysis. In the first axis, called “the SUS you see”, we analyzed 72 news published by TV Asa Branca. The main themes found were: Vaccination, Good Practices in Unidades de Saúde da Família, Bottlenecks in Unidades de Saúde da Família and Improvements in the infrastructure of Unidades de Saúde da Família. In the second axis, called “the SUS that is NOT seen”, we present the absent themes in the station's news. In order to make this analyses, we used the theoretical framework of Newsworthiness Criteria (Traquina, 2005, 2008), (Wolf, 2005); (Silva, 2005, 2018); Regional Media (Pinto, 2015), (Dorelles, 2013), (Bueno, 1977, 2013), (Vasconcelos, 2010), (Boaventura, 2016); Unified Health System - SUS (Paim, 2013), (Aguiar, 2015), (Pinto, 2019); Communication and Health (Araújo, 2014), (Cardoso, 2014), (Paim, 2008). The result of the research found that there was a mismatch between the advances that Caruaru conveyed regarding Basic Health Care and the news on TV Asa Branca.